THE EFFECT OF COACH LEADERSHIP, TEAM COOPERATION, AND ACHIEVEMENT MOTIVATION ON THE PERFORMANCE OF THE DEPOK CITY ATLET - Muhammad Fahmi (FT-TEKNIK USNI, 2019)
The objective of this research was to examine and analyze the effect of coach leadership, teamwork, and achievement motivation on the performance of Depok city’athletes, It was a quantitative research with associative approach, conducted at DepokNational Sports Committee (KONI). The data were collected through questionnaire involving 203 samples of respondent of athletes and coach among Depok National Sports Committee. Data collection techniques carried out in this study were using questionnaireinstruments. The questionnaire used consisted of questionnaires, variables of coach leadership, teamwork, achievement motivation and athlete's performance. The type of questionnaire is a closed questionnaire where the questionnaire distributed to respondents has provided the answer in the form of five answer choices, so the respondent just has to choose one of the five answers provided. The measurement scale of the coach leadership questionnaire, teamwork, achievement motivation and athlete's performance used a Likert scale. The primary data collected then through the estimated error normality test, linearity test and significance test. Then analyzed and tested the hypothesis using path analysis. Data analysis techniques in this study include: (1) descriptive data analysis, (2) requirements test, (3) inferential data analysis.The data analysis and interpretation indicates that: (1) Coach’ leadership has no direct effect on athletes’ performance. (2) Coach’ leadership has no direct effect on achievement motivation. (3) Coach’ leadership has direct effect on teamwork. (4) Teamwork has direct effect on achievement motivation. (5) Teamwork has direct effect on athletes’ performance. (6) Achievement motivation has direct effect on athletes’performance. (7) Coach’ leadership has no indirect effect on athletes’ performance through achievement motivation. (8) Coach’ leadership has an indirect effect on athletes’ performance through teamwork. (9) Coach’ leadership has an indirect effect on athletes’ performance through teamwork and achievement motivation